Experimental Verification of Nonlinear Position-Flux Zero-Bias Control for Heteropolar Active Magnetic Bearing - Arkadiusz Mystkowski; Andrzej Kierdelewicz (Applied Computational Electromagnetics Society Journal (ACES), 2019)
This study presents experimental verification of a nonlinear position-flux control for active magnetic bearing (AMB) system operated with zero-bias flux. Recently developed controllers for nonlinear fluxcontrolled AMB applications are complicated and inherently difficult to implement. Therefore, three designs of low-order controllers are proposed using nonlinear feedback tools including Lyapunov-based techniques and control Lyapunov functions (CLFs). The control objective is to globally stabilize the rotor mass position in the AMB system. Responses of the AMB system states to initial condition and to external load disturbance are presented and the simulation and experimental results for transient responses are compared. The overshoots are compensated for the zero neighbourhood, and the rotor position amplitude does not exceed 2.5% of the air gap.